Modeling the Fate and Distribution of Floating Litter Particles in the Aegean Sea (E. Mediterranean) - Politikos, Dimitrios V.; Ioakeimidis, Christos; Papatheodorou, George; Tsiaras, Kostas (Frontiers in Marine Science, 2017)
A circulation model is coupled to a Lagrangian particle-tracking model to transport floating litter particles in the Aegean Sea, Greece (Eastern Mediterranean). Considering different source regions and release dates, simulations were carried out to explore the fate and distribution of floating litter over 1990-2009, taking into account the seasonal and interannual variability of surface circulation. Model results depicted recurrently high concentrations of floating litter particles in the North Aegean plateau, the Saronikos Gulf, and along Evia and Crete islands. Modelled transport pathways of floating litter demonstrated that source regions are interconnected, with Saronikos Gulf being a main receptor of litter from other sources. Notably higher percent of litter exit (~35%) than enter the model domain (~7%) signified that Aegean Sea seems to act as a source rather than receptor of floating litter pollution in the Eastern Mediterranean Sea. Beached litter was found around 10%, mostly located in the western part of the Aegean Sea. This is the first modelling study to explore the transport of floating marine litter in Greek waters.